Tradiciones y costumbres en la comunidad Santa Teresita de Guabug, parroquia San Juan, cantón Riobamba y su transformación hasta la actualidad. - Lema Majin, Evelyn Karolina (2024)
The present research titled "Traditions and Customs in the Santa Teresita de Guabug Community, San Juan Parish, Riobamba Canton, and their Transformation to the Present Day" aims to analyze the main factors of cultural transformation through the description of traditions and customs, the identification of key factors, and the study of cultural representations. It is made clear that the preservation of cultural heritage is key for communities, reflecting their identity over time. Despite globalization and technology driving changes, communities like Santa Teresita de Guabug in Ecuador maintain their roots through religious, agricultural, and artistic practices passed down through generations. Adapting to these changes is essential to keep the history and identity of communities alive. The methodology employed considers an anthropological qualitative approach to understand the traditions and customs of the Santa Teresita de Guabug community. Bibliographic and descriptive techniques are used, with a non-probabilistic research design. Interviews and field studies are employed to gather data from a sample of thirty community members, while ethnographic methods will be used to analyze cultural practices and understand cultural transformation in depth. Among the most significant results, the importance of preserving local traditions while adapting to a changing world is highlighted. There is a recognition of the need to find a balance between conserving cultural heritage and integrating modern innovations, promoting intergenerational collaboration and intercultural education as means to keep community identity alive. Thus, it is concluded that despite challenges such as globalization and youth migration, the community demonstrates a notable capacity for adaptation and preservation. However, it is suggested to establish a committee dedicated to the management of cultural heritage to find a balance between conservation and cultural adaptation.